2016
DOI: 10.1021/acsnano.5b07355
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Exfoliated SnSe Nanosheets and Their SnSe/Poly(3,4-ethylenedioxythiophene):Poly(styrenesulfonate) Composite Films for Polymer Based Thermoelectric Applications

Abstract: PSS. The fabricated SnSe NS/PEDOT:PSS composites show a maximum figure of merit (ZT) of 0.32 at a SnSe NSs loading of 20 wt %. The mixing of inorganic nanoparticles with the conducting polymer matrix forms products with extremely low thermal conductivities, which is a promising strategy for the realization of polymer based efficient thermoelectric applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
176
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(182 citation statements)
references
References 45 publications
3
176
0
3
Order By: Relevance
“…Some inorganic materials such as carbon nanotubes [132,133], traditional inorganic TE fibers [134,135], metallic nanowires [136,137,138], and so on, have been applied as inorganic components to achieve high enhancement of the Seebeck coefficient and/or electrical conductivity in the conductive polymers. Meanwhile, many conductive inorganic/insulating organic NCs have been studied [139,140,141], in which the infinite conductive path is formed when the volumetric fraction of the inorganic materials is beyond the critical volume fraction according to the percolation theory [142,143,144].…”
Section: Nanocomposites For Thermoelectricitymentioning
confidence: 99%
“…Some inorganic materials such as carbon nanotubes [132,133], traditional inorganic TE fibers [134,135], metallic nanowires [136,137,138], and so on, have been applied as inorganic components to achieve high enhancement of the Seebeck coefficient and/or electrical conductivity in the conductive polymers. Meanwhile, many conductive inorganic/insulating organic NCs have been studied [139,140,141], in which the infinite conductive path is formed when the volumetric fraction of the inorganic materials is beyond the critical volume fraction according to the percolation theory [142,143,144].…”
Section: Nanocomposites For Thermoelectricitymentioning
confidence: 99%
“…For example, PEDOT composites generate zT = 0.42 at room temperature, which is comparable to those of some traditional inorganic materials [6,[16][17][18][19][20]. Organic/inorganic hybridization is another promising way to improve the thermoelectric performance of polymers [21][22][23]. Zhang et al [24] reported that the template-directed in situ polymerization preparation of nanocomposites of PEDOT:poly(4-styrenesulfonic) (PSS) coated with multiwalled carbon nanotubes (MWCNTs) can enhance the thermoelectric properties.…”
Section: Introductionmentioning
confidence: 96%
“…Similar approach can be adopted for other metals such as Mo, Sn composite with PEDOT:PSS for applications in different areas such as thermoelectric, anode materials for lithium-ion batteries etc. [133,134]. Another research group reported the exfoliation of MoS 2 nanosheet in PEDOT:PSS solution by sonication mixing [135].…”
Section: Cp/metal Chalcogenides Nanocompositesmentioning
confidence: 99%